Wind Load and Wind Vibration Response of a TV Tower Based on Force Measurement Test in a Wind Tunnel - Daqiao Xia; Kangfu Peng (Advances in Civil Engineering)
Television towers have a complex aerodynamic shape and low damping characteristics. As such, the wind load and the wind induction response are key factors in their design and maintenance. To study these two parameters of high-rise TV towers, a wind tunnel force test was conducted at a height of 280 m using the Foshan TV tower as a model. The TV tower model was divided into seven detachable sections. Three wind fields with different turbulence intensities were simulated in the wind tunnel, corresponding to different sections, and lateral force tests were performed on each section using a high-frequency dynamic balance. The experimental results were used to calculate the wind-induced response when considering the modal (first three-order) coupled response and were compared with the wind-induced response calculated using the complete quadratic combination (CQC) method. The results revealed that equivalent static wind loads (ESQL) and CQC calculation methods were used in this study, and a higher degree of coincidence was observed, which may be useful in engineering practice.